Blood transfusion safety: A study of adverse reactions at the blood bank of a tertiary care center - Negi, Gita (Adv Biomed Res, 2015)
BACKGROUND: An adverse transfusion reaction (ATR) is an unfavorable reaction to the transfused unit, the severity of which may be different among individuals depending upon the type of reaction and the patient's susceptibility. Transfusion reactions may be immediate or delayed type depending on the onset and immune or nonimmune type depending on the pathogenesis. A study was conducted to study the frequency of various transfusion reactions and the associated morbidity. MATERIALS AND METHODS: All ATRs occurring over a period of 3 years at a tertiary care health center were studied in detail according to the institute's protocol. RESULTS: Of 38,013 units of blood and components that had been issued, 101 (0.2%) cases had an ATR. The most common reaction was allergic - 34/101 (33.6%) followed by febrile - 26/101 (25.7%). Other reactions included transfusion-related acute lung injury in 6/101 (5.9%) cases, and immune reactions were seen in 19/101 (18.8%) cases. CONCLUSION: Allergic and febrile reactions are most common and least harmful, but fatal reactions can also occur, and preventive measures must be taken to avoid such reactions.